The Relationship between Articulation and Discrimination of Kannada Speech Sounds in Terms of Distinctive Features - KUMUDAVALLI S (Journal of All India Institute of Speech and Hearing, 1970)
Little is known about the relationship between articulation and discrimination in phonological developlnent. Winitz (1969) has suggested that the child's understanding of the adult phoneme system or a portion thereof antedates any attempt by him to utter language units. In the adsence of unequivocal evidence, many have assumed that articulatory errors reflect impairment in the development of speech sound discrimination. To test this hypothesis, the relationship between articulatory performance and discrimination has been investigated. Articulatory defectives have been found to be inferior to articulatory non-defectives on tests of discrimination.